Government Policy in Eradication of Illegal Fishing Practices - Putri, Nur Annisa; Selviani, Evi; Nurdin, Elmiati; Febriyanti, Nur Ilmi Putri; Yoesry, Erni (International Journal of Business, Law, and Education, 2026)
Indonesia, as an archipelagic state, possesses vast marine territory with significant fisheries potential, yet faces serious challenges from illegal, unreported, and unregulated (IUU) fishing. This practice causes substantial economic losses, environmental degradation, and social inequality among local fishers. This study aims to examine the impacts of illegal fishing and analyze government policies addressing the issue. The research uses a normative legal method with a statutory approach. Findings show that illegal fishing leads to overfishing, ecosystem destruction, and reduced fish catch for small-scale fishers. The Indonesian government has implemented various policies, including the National Plan of Action (NPOA) to combat IUU fishing, and established a Joint Task Force supported by coordinated sea surveillance through Monitoring, Control, and Surveillance (MCS). However, limitations in human resources and funding remain significant obstacles in monitoring Indonesia’s vast waters. To address this, the government encourages community involvement through the formation of Community Surveillance Groups (Pokmaswas). Synergy between central and local governments, local communities, and international cooperation is essential for sustainable marine resource management. The implementation of responsible fishing practices, in accordance with the Code of Conduct for Responsible Fisheries (CCRF), is crucial to ensure the sustainability of Indonesia’s marine resources for current and future generations.